Traditional Ethno-Medicinal Plants Used for Treatment of Diabetes by Bhuyan Tribes in Sundargarh District of Odisha, India-An Ethnobotanical Survey - Das, Julie; Acharya, Baman Chandra; Mallick, Samarendra Narayan (Plant Science Today, 2023)
Diabetes mellitus is the most common disease which has conveyed significant well-being intimidation around the world. The accessible synthetic drugs for the fix of Diabetes mellitus are related to significant expense, different incidental effects and a few constraints. Medicinal plants are the storehouse of the phytochemicals which can be helpful for the therapy of various ailments. Medicinal and aromatic plants are the better option in contrast to compound medications with little or no side effects. Ethnomedicinal studies carried out among the Bhuyan tribal groups in the Sundargarh region, Odisha for the investigation of antidiabetic treatments. The Bhuyan tribal group has a rich knowledge of plants which are used in the treatment of different disease causes. The ethnomedicinal data was gathered from interviews and field studies with nearby healers and townspeople. Restorative plants were gathered and related to help from native healers. These kind medicines have been displayed to have huge mending power, either in their normal state or as the wellspring of new items handled by them. Our study is mainly concentrated on plants used by Bhuyan tribal groups in relation to the cure of diabetes. An extensive field survey of different parts of the district was made with the local tribal villagers and ethnomedicinal or ayurvedic drug practitioner’s perusal of published literature and herbarium specimen of different herbaria of the district was done. A sum of 25 plants having a place with 18 unique families used to treat diabetes utilized by Bhuyans of Sundargarh district has been reported. In this report we have prepared detailed notes on the method of preparation of precise doses, the part/parts of plants used and the method of application of doses with scientific names, vernacular names and family names of collected plants are also given. Further, it emphasizes strongly in this regard the optional and rational uses of traditional and natural indigenous medicine. The results of this study showed that these tribal people still depend on medicinal plants in Sundargarh district forest areas. The study thus underlines the potential of ethnobotanical research and the need for the documentation of traditional ecological knowledge pertaining to medicinal plant utilization for the greater benefit of mankind.